Labor capital development of the region in the focus of sociological research: factors and problems - A. G. Karimov; S. S. Selivanova; R. G. Fatkullina (Вестник университета)
The presented work analyzes the features, problems and factors of labor capital development of the Republic of Bashkortostan based on the data of a sociological study conducted by the Institute for Socio-Economic Research of the Ufa Federal Research Center of the Russian Academy of Sciences in 2021. A number of problems faced by the able-bodied population are considered, including: a relatively low standard of living of the population, which hinders the provision of the quality of life and professional productivity of workers; gender inequality in the distribution of labor incomes of the population; the predominance of negative assessments of the able-bodied population of their physical condition, the quality of their leisure and vacations; discrepancy between the high qualification of employees and the functions performed, which does not allow them to fully realize their labor potential in the workplace. Particular attention is paid to the analysis of values that prevail in the minds of the able-bodied population and determine their labor behavior, and as a result, have a negative impact on the formation of labor capital. Thus, it was revealed that the value orientations of the population of the Republic of Bashkortostan are typical for countries of “catching up” development. In this regard, the authors substantiate the necessity of cultivating the values of rationality of financial thinking, equality, self-expression and autonomy, as well as improving institutions that support these values in society. These values act as factors in the formation of high-quality labor capital in the conditions of modern Russia